Geoenvironmental mapping as a subsidy for the selection of areas for implantation of urban solid waste treatment centers: Application to the Santa Cruz da conceição municipality, São Paulo state - Brito, Hermes Dias [UNESP]; Reis, Fábio Augusto Gomes Vieira [UNESP]; Corrêa, Claudia Vanessa dos Santos [UNESP] (UNESP - Universidade Estadual Paulista, 2018)
This study presents and discusses the development of a geo-environmental mapping focused on the proper selection of areas for the implementation of Solid Waste Treatment Center (SWTPs), with the application focus on the municipality of Santa Cruz da Conceição, a town in São Paulo State, which presents significant environmental nonconformity in relation to management solid waste and disposal of waste. The integration of information obtained from the literature performed, the generation of database (physical, biological and socio-economic elements) and multi-criteria analysis in GIS led to the preparation of this mapping. This work had as fundamental element a previously established physiographic compartmentalization of the area, and considered mainly the aspects of permeability, erosion resistance and stability to gravitational movements. Database was integrated with information on fragments of vegetation, slope, and poultry risk management areas in regional aerodromes, information on municipal laws, and legal and technical standards. Among the results obtained, there is, centrally, the definition of areas for setting up SWTPs, including incinerators and landfills (in ditches and in layers). This study provides elements for discussion and decision-making related to the implementation process of waste treatment plants and projects associated with them, being applicable to other municipalities.
Mapeamento geoambiental como subsídio seleção de áreas para implantação de centrais de tratamento de resíduos sólidos urbanos: Aplicação ao município de Santa Cruz da conceição-SP
Keywords: Engineering Geology; Locational Alternatives Study; Multicriteria Analysis; Sustainable Land Management